2013
DOI: 10.1111/j.1475-4959.2012.00486.x
|View full text |Cite
|
Sign up to set email alerts
|

Documenting glacial changes between 1910, 1970, 1992 and 2010 in theTurgenMountains,MongolianAltai, using repeat photographs, topographic maps, and satellite imagery

Abstract: The Turgen Mountains lie in northwestern Mongolia, roughly 80 km south of the Russian border. The area was visited in 1910 by a Royal Geographical Society expedition led by Douglas Carruthers. The party undertook an extensive survey of the range and also documented the extent of the glaciers with photographs. One hundred years later, in summer 2010, a US-Mongolian expedition retraced portions of the 1910 expedition. Camera locations were matched to the historical photographs and repeated photographs taken. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…Later, the glaciation of Mongolia was studied by Baast [30]. In the 21st century, the development of remote sensing, sometimes in combination with in situ observations, led to a number of new publications: [31][32][33][34][35][36][37][38][39] The Mongolian glaciers have been cataloged and mapped by Kamp et al [34,40]. Recently the glaciers of the region were included in the GLIMS (Global Land Ice Measurements from Space) database and the Randolph Glacier Inventory [34,41,42].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Later, the glaciation of Mongolia was studied by Baast [30]. In the 21st century, the development of remote sensing, sometimes in combination with in situ observations, led to a number of new publications: [31][32][33][34][35][36][37][38][39] The Mongolian glaciers have been cataloged and mapped by Kamp et al [34,40]. Recently the glaciers of the region were included in the GLIMS (Global Land Ice Measurements from Space) database and the Randolph Glacier Inventory [34,41,42].…”
Section: Introductionmentioning
confidence: 99%
“…Recently the glaciers of the region were included in the GLIMS (Global Land Ice Measurements from Space) database and the Randolph Glacier Inventory [34,41,42]. The materials of the field observations were obtained for Turgen [33], Tavan Bogd, and Tsambagarav [37,43,44]. The first overview of the present glaciations of the arid Altai, including both the Russian and the Mongolian territory were given in our previous article [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies of contemporary glaciation in the Altai Mountains have focused upon individual mountain ranges and massifs (e.g. Kamp, McManigal, Dashtseren, & Walther, 2013). For example, Kamp et al (2013) estimated the total glacier coverage of the Ikh-Turgen massif ( Figure 2) as 31.8 km 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Information on the utilised data and the stations locations is given in Sect. 3.1 Dulamsuren et al 2014;Schluetz and Lehmkuhl 2007;Schwikowski et al 2009) and its impact on glaciers (Kamp et al 2013) and forests. Most tree ring-based past climate reconstruction studies in Western Mongolia (Davi et al 2015;Davi et al 2009) and north-western China (Chen et al 2012(Chen et al , 2014Zhang et al 2015) identified a significant climate and environmental change with rapid warming and precipitation increases caused by a general intensification of the global hydrological cycle.…”
Section: And Clemens Simmermentioning
confidence: 99%